2008
DOI: 10.1523/jneurosci.1189-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Motor Neuron Regeneration in Adult Zebrafish

Abstract: The mammalian spinal cord does not regenerate motor neurons that are lost as a result of injury or disease. Here we demonstrate that adult zebrafish, which show functional spinal cord regeneration, are capable of motor neuron regeneration. After a spinal lesion, the ventricular zone shows a widespread increase in proliferation, including slowly proliferating olig2-positive (olig2 ϩ ) ependymo-radial glial progenitor cells. Lineage tracing in olig2:green fluorescent protein transgenic fish indicates that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
337
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 243 publications
(370 citation statements)
references
References 30 publications
31
337
1
1
Order By: Relevance
“…Our data were in good agreement with previous findings in the adult zebrafish brain, reporting that the number of newly-generated neurons is extremely low in the region where descending neurons exist (Zupanc et al, 2005;Hinsch and Zupanc, 2007). In contrast to the upper motor neurons in the brainstem, motor neurons in the spinal cord become apoptotic after SCI, and neurogenesis from the ependymal zone around the central canal is activated via sonic hedgehog and/or Notch signaling (Reimer et al, 2008;Reimer et al, 2009;Dias et al, 2012).…”
Section: Long-term Survival Of Upper Motor Neurons In the Nmlf And Imsupporting
confidence: 93%
See 2 more Smart Citations
“…Our data were in good agreement with previous findings in the adult zebrafish brain, reporting that the number of newly-generated neurons is extremely low in the region where descending neurons exist (Zupanc et al, 2005;Hinsch and Zupanc, 2007). In contrast to the upper motor neurons in the brainstem, motor neurons in the spinal cord become apoptotic after SCI, and neurogenesis from the ependymal zone around the central canal is activated via sonic hedgehog and/or Notch signaling (Reimer et al, 2008;Reimer et al, 2009;Dias et al, 2012).…”
Section: Long-term Survival Of Upper Motor Neurons In the Nmlf And Imsupporting
confidence: 93%
“…BrdU incorporation assay was performed to visualize cell proliferation, as described previously (Reimer et al, 2008). In brief, fish were anesthetized and intraperitoneally injected with 50 µl of 2.5 mg/ml BrdU (Sigma-Aldrich) at 0, 2 and 4 days post-lesion (dpl).…”
Section: Intraperitoneal Application Of Brdumentioning
confidence: 99%
See 1 more Smart Citation
“…However, in zebrafish S100b-positive cells, as previously shown (Mä rz et al, 2010), co-express the radial glial markers BLBP and GFAP suggesting that these cells belong to the radial glial lineage.In the zebrafish adult spinal cord, Tg(olig2:EGFP)-positive cells are distributed in the gray and white matter and, in addition, radial glia-like cells at the central canal express olig2 (Park et al, 2007). Moreover, it was shown that these Tg(olig2:EGFP)-positive radial glialike cells act as progenitors of motor neurons in the regenerating spinal cord (Reimer et al, 2008), while they produce mostly glial cells in the uninjured spinal cord (Park et al, 2007). As none of the ventricular olig2-expressing cells of the telencephalon co-expresses sox10, it remains to be investigated whether these cells are indeed progenitors of oligodendrocytes or whether they give rise to neurons as in the regenerating spinal cord.…”
Section: Olig2-expressing Cells At the Ventricular Zone Of The Telencmentioning
confidence: 99%
“…A recent study found that slowly proliferating Tg(olig2:EGFP)-positive radial glia-like cells are present in the adult zebrafish spinal cord, where they seem to act as progenitors restricted to the oligodendrocyte lineage (Park et al, 2007). Interestingly, when the spinal cord is injured, these cells not only produce oligodendrocytes but also motorneurons (Reimer et al, 2008).…”
Section: Introductionmentioning
confidence: 99%